Clinical Efficacy of Wrinkle Improvement Right After using Antiaging Cosmetics containing Palmitoyl-GHK-R4 Peptide (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
GHK (gly-his-lys), which was first isolated from human serum and known as a hepatocellular growth factor, is a typical wrinkle improving functional peptide. Pal-GHK is a form of GHK containing palmitate, which increases skin permeability and stability of GHK. However, the problem is that GHK has difficulty in penetrating stratum corneum due to its hydrophilic properties, making it difficult to actually exhibit efficacy in the skin. In this study, Arg 4, one of the skin penetrating peptides, was conjugated with Pal-GHK to get palmitoyl heptapeptide, Pal-GHK‐R4, and clinical trials were conducted on the wrinkle improvement effect of cosmetics containing Pal-GHK‐R4. As a result of total 21 subjects used the test products on the face area; 1) measurement value of crow’s feet statistically significantly decreased right after using the test products compared to before using the products (p